Co słychać w manifestach? - Karpowicz, Agnieszka (Zagadnienia Rodzajów Literackich, 2019)
The text proposes an experimental reading of the manifestos of the first Polish futurists in line with the “listening to literature” project (Andrzej Hejmej). I look for traces of the audiosphere associated with the human voice in the manifestos and ephemeral prints in which they were published in 1921. I try to reconstruct them using the recontextual method, by outlining the discursive field of the era in which they were created. Asking about the possibility of reconstructing the audiosphere on the basis of historical texts, I point to screaming and shouting as the main voice practices of the interwar period and I make a connection between them and the language of the press and politics as well as subversive communication strategies.